2021
DOI: 10.1108/md-01-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation and firm performance: can there be too much of a good thing?

Abstract: PurposePast research has generally purported that market orientation (MO) leads to superior firm performance, despite emerging evidence suggesting that the highest levels of MO are not always rewarded. Drawing on resource-based view and MO literature, the authors posit that too much MO may be as detrimental as too little for firms seeking to achieve better performance, and that moderate MO capabilities may be the most beneficial. Furthermore, the authors propose and test for organizational confidence as a firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…However, recent theoretical development proposed adaptive marketing capabilities (AMC indicated that market orientation correlates with firm international performance. Nevertheless, Jancenelle et al (2021a) discovered in a fiveyear longitudinal sample of enterprises that firms with the highest concentrations of market orientation are not necessarily rewarded the most in terms of superior performance in international markets. As Jancenelle et al (2021b) report that an inverted U-shaped relationship between market orientation capability and performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent theoretical development proposed adaptive marketing capabilities (AMC indicated that market orientation correlates with firm international performance. Nevertheless, Jancenelle et al (2021a) discovered in a fiveyear longitudinal sample of enterprises that firms with the highest concentrations of market orientation are not necessarily rewarded the most in terms of superior performance in international markets. As Jancenelle et al (2021b) report that an inverted U-shaped relationship between market orientation capability and performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Nevertheless, Jancenelle et al (2021a) discovered in a fiveyear longitudinal sample of enterprises that firms with the highest concentrations of market orientation are not necessarily rewarded the most in terms of superior performance in international markets. As Jancenelle et al (2021b) report that an inverted U-shaped relationship between market orientation capability and performance. Therefore, this study suggested that: H1: Market orientation has a significant relationship with international performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%